Ferris - DiCamillo, Kate (Candlewick Press, 2024)
During the summer before fifth grade, Ferris Wilkey has her hands full with her little sister terrorizing the town, her Aunt Shirley moving into their basement and her grandmother seeing a ghost--one who has wild, impractical and illuminating plans.